RADT-26. PROTON VERSUS PHOTON CRANIOSPINAL IRRADIATION FOR ADULT MEDULLOBLASTOMA: A DOSIMETRIC AND TOXICITY ANALYSIS. (12th November 2021) - Breen, William; Geno, Connie; Harmsen, William; Brown, Paul; Waddle, Mark; Qian, Jing; Burns, Terence; Ruff, Michael; Neth, Bryan; Yan, Elizabeth; Laack, Nadia; Mahajan, Anita
Abstract: Medulloblastoma is a posterior fossa tumor rarely diagnosed in adults. Treatment includes craniospinal irradiation (CSI). Proton CSI is increasingly utilized to decrease radiation dose to normal tissues, despite the lack of randomized data demonstrating decreased toxicity compared to photon CSI. This single institution retrospective study of 39 adult medulloblastoma patients includes nineteen patients treated with photon CSI prior to 2015, and twenty treated with proton CSI thereafter. Median age was 28 years (range 18-66). Molecular subtype was most commonly sonic hedgehog (68%). The most common fractionation schedule was 36 Gy CSI in 20 fractions (85% of photon and 58% of proton patients) with a boost to 54-55.8 Gy (92%). Proton CSI delivered significantly lower mean doses to the cochleae (median 32 Gy vs. 44 Gy), lacrimal glands (8 vs. 36 Gy), lens (2 vs. 28 Gy), parotid glands (3 vs. 26 Gy), pharyngeal constrictors (6 vs. 15 Gy), esophagus (2 vs. 29 Gy), heart (0 vs. 14 Gy), lungs (1 vs. 7 Gy), liver (0.1 vs. 7 Gy), and skin (38 vs. 51 Gy) (all p< 0.001). Patients receiving proton CSI had significantly lower rates of acute dysphagia of any grade (5% vs. 35%, p= 0.044) and decreased median weight loss during radiation (+1.0 vs. -2.8 kg, p= 0.011). Acute hospitalization was associated with increased weight loss (p= 0.009). Median follow-up was 2.9 and 12.9 years for proton and photon patients, respectively, limiting late toxicity and outcome comparisons. At last follow-up five photon patients had died (two of progressive disease, three without recurrence ages 41-63) and 21% had experienced major cardiovascular events. At 10 years, 89% were alive and 82% were recurrence free. In conclusion, this study demonstrates dosimetric improvements with proton CSI, potentially leading to decreased acute toxicity including dysphagia and weight loss during treatment.